Traditional Sushi for Modern Consumers: A Comparison Between Sushi Consumption Behavior in Japan and Norway. Issue 6 (17th August 2016) - Altintzoglou, Themistoklis; Heide, Morten; Wien, Anders H.; Honkanen, Pirjo
ABSTRACT: This study focused on differences between uses and users of sushi and sashimi in Norway and Japan. The study was based on a consumer survey that was completed by a representative sample of 902 participants from Norway and 897 participants from Japan. The survey included questions about food consumption frequency, ways of sourcing sushi and sashimi and situational factors related to consumption. Participants also reported their knowledge about, attitudes toward, and ambivalence related to sushi and sashimi, social acceptability of sushi and sashimi consumption, domain-specific innovativeness, and social and demographic characteristics. Differences in sushi consumption behavior between Japanese and Norwegian consumers considering the situational parameters surrounding sushi and sashimi consumption were revealed. Considerations for future research and implications on export strategy development were discussed.